KEANEKARAGAMAN BIVALVIA DAN PERANANNYA SEBAGAI BIOINDIKATOR LOGAM BERAT KROMIUM (CR) DI PERAIRAN KENJERAN, KECAMATAN BULAK KOTA SURABAYA - AMANDA PUTRI, RESTU Amanda (LenteraBio: Berkala Ilmiah Biologi, 2012)
The Kenjeran Water is one of the marine tourism in Surabaya. It is located in the fishing village of Tambak Deres. Diversity in the Kenjeran Water is very diverse, one of it is the types of bivalves. As a place for recreation, Kenjeran Water are susceptible to contamination due to the human activity comes from the domestic waste. Consequently, many heavy metals have been entering the water. The existence of marine organisms such as bivalves can be used as a bioindicator of the water quality. This study was a descriptive study, using survey and observation. Implementation began in November-December 2011 with the method of transect for each station, per 100 metre area of Kenjeran Water Surabaya, which is representative to serve as a habitat for bivalves and to measure the water quality. The result of this study indicated that The Kenjeran Water Surabaya have 6 species, among of them are Perna viridis, Trisidos tortuosa, Mactra chinensis, Mercenaria mercenaria, Anadara granosa and Anadara floridana. The highest indices of diversity and abundance were 1.978 and 37.702. The average levels of chromium in the water, sediment, and the meat was 0.052 mg/l; 22.71 mg/l; and 49.25 mg/l. Based on analysis of chromium contamination, the Kenjeran Coastal?s water were polluted with chromium on medium level. Its Bivalves are unfit for consumption. Based on this, the bivalves are a bioindicator for Cr polluted waters.